Pengaruh Penerapan Model Problem Based Learning Berbasis Socio-Scientific Issue Pada Materi Sistem Pernapasan Terhadap Kemampuan Berpikir Kritis Siswa SMA - Yunita Cahya Rani; Afreni Hamidah; Husmayani Muny Putri (UNIB Press, 2026)
This study aims to determine the effect of implementing a Problem-Based Learning (PBL) model based on Socio-Scientific Issues (SSI) on respiratory system material on students’ critical thinking skills. The method used is a quantitative approach with a quasi-experimental design and a non-randomized control-group pre-test post-test design. The research subjects were 11th-grade students in Class F at SMAN 6 in Jambi City, with an essay test used as the instrument to measure critical thinking skills. Data analysis was conducted using a One-Way ANCOVA test to determine the significant effect of the treatment. The results showed that the implementation of SSI-based PBL had a significant effect on improving students’ critical thinking skills compared to the PBL model alone, with an effect size of 0.76, which falls into the large category. Thus, the SSI-based PBL model can serve as an effective learning alternative to enhance high school students’ critical thinking skills.